PALEO-ENVIRONMENTAL EVOLUTION AS REVEALED BY ANALYSIS OF ORGANIC CARBON AND NITROGEN: A CASE OF COASTAL TAIPEI BASIN IN NORTHERN TAIWAN - Ku H.-W.; Chen Y.-G.; Chan P.-S.; Liu H.-C.; Lin C.-C. (My University, 2007)
In an attempt to discriminate different sources of organic matter and reconstruct the paleo-environment of the Taipei Basin, northern Taiwan over the past 250,000 years, organic carbon and nitrogen content (C/N ratios) and isotope compo- sition (δ13C and δ15N) are measured for sediment samples collected from core Wu-ku drilled at the depocenter in western Taipei Basin. The high δ13C values (up to -17.0‰) and high C/N ratio (up to 14.9 and 13.0, respectively) indicate that this area underwent a period of relative aridity during MIS 2 and mid MIS 6. Another two periods of high and variable δ15N values (up to 15.5 and 13.5‰, respectively) in MIS 1 and MIS 7 represent different nutrient condition in the basin. In MIS 1, high δ15N variability along with increasing TOC may reflect an unstable trend of aquatic productivity related to the dynamic mixing ratios of seawater and fresh water. The high δ15N values observed in the sediments of MIS 7 could be explained by the employment of a 15N-enriched nitrate from denitrification as the main source of nitrogen for primary producers.
Keywords: C/N RATIOS; ORGANIC MATTER; TAIPEI BASIN; δ13C; δ15N